2016
DOI: 10.1007/s00422-016-0704-8
|View full text |Cite
|
Sign up to set email alerts
|

Robustness, flexibility, and sensitivity in a multifunctional motor control model

Abstract: Motor systems must adapt to perturbations and changing conditions both within and outside the body. We refer to the ability of a system to maintain performance despite perturbations as “robustness,” and the ability of a system to deploy alternative strategies that improve fitness as “flexibility.” Different classes of pattern-generating circuits yield dynamics with differential sensitivities to perturbations and parameter variation. Depending on the task and the type of perturbation, high sensitivity can eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 85 publications
2
70
0
Order By: Relevance
“…As we have shown, animals may extend the duration of the power stroke (retraction) of swallowing when load is encountered. This is consistent with predictions made by a nominal neuromechanical model of Aplysia feeding (Shaw et al, 2015;Lyttle et al, 2017). Similarly, in vertebrate and stick insect locomotion, increased load during the stance phase causes increased excitation to the leg extensor muscles (Pearson, 1995).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As we have shown, animals may extend the duration of the power stroke (retraction) of swallowing when load is encountered. This is consistent with predictions made by a nominal neuromechanical model of Aplysia feeding (Shaw et al, 2015;Lyttle et al, 2017). Similarly, in vertebrate and stick insect locomotion, increased load during the stance phase causes increased excitation to the leg extensor muscles (Pearson, 1995).…”
Section: Discussionsupporting
confidence: 88%
“…More generally, animals will associate different foods with different levels of reward and seek out their preferred foods (Petrovich, 2018). Many of the medium-and long-term behavioral adaptations that animals exhibit are forms of flexibility, through which they remain robust to environmental variation and maintain high fitness (Lyttle et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The third example (Section 3.3) is a 2-D Glass network, a PWL system obtained as the singular limit of a class of models for feedback inhibition and gene regulatory networks [19]. The fourth example (Section 3.4) is a 3-D PWL system arising as a simplification of a nominal central pattern generator model for regulation of feeding motor activity in the marine mollusk Aplysia californica [37,54] and related to a Lotka-Volterra system with three populations [44]. In the final two examples, we extend our theory to the case of weakly coupled oscillators (Section 4.1).…”
Section: Resultsmentioning
confidence: 99%
“…Much like many studies on flexibility [11,9,38] we can switch between these functionality easily, with either changes in synaptic weights constant inputs or changes in bias current. Again, we showed that while many of these functions can exist without mutual inhibition; they cannot coexist with other functions.…”
Section: Co-existence Of Functionsmentioning
confidence: 99%